Snuffed out (Magic candle shop mystery, 1,, 2023)
Fraternal twins Tabby and Sage Winslow own The Book and Candle Shop in Savannah. Sage is hot-headed and impulsive while Tabby is calm and collected, making them the perfect partnership. Blithe McAdam had been seen in a heated argument with shop clerk Gerard-- and later found dead from a blow to the heat. The twins are convinced of Gerard's innocence and start digging into Blithe's past. The neighbor who found the body isn't talking, medical examiner Quig won't give any details about the autopsy, and nasty rumors begin surfacing about the drowning of Blithe's father years earlier. With the clock ticking, the twins find themselves in the grip of an unseen and deadly energy that has seeped into their midst-- and into the sights of a ruthless killer. -- adapted from jacket

In the wick of time (Magic candle shop mystery, 2,, 2023)
December in Savannah, Georgia, is a sight to behold. With all the festivities--including the traditional riverfront luminary display during the boat parade--twin sisters Tabby and Sage Winslow are busier than ever setting up for the big celebration. But that isn't the only thing on the sisters' minds. Both Sage and her fellow employee Mary Nicole are vying for the sought-after assistant manager job at the plant nursery. But when Loren Lee, their boss, is found dead, and Sage becomes the police's favorite suspect, both Winslow girls know that they'll need more than a flicker of magic and their sisterhood to solve the murder and clear Sage's name. Soon, Tabby realizes that this is just one of the many problems they have. If being a suspect for murder wasn't enough, there are more magical problems that they have to fix: Sage's boyfriend is having a paranormal experience of his own he can't control, there's an energy vampire searching for his supposedly lost cousin, her cat suddenly dislikes her, and oh--every time Tabby hiccups, she turns completely invisible. The suspect list grows with each day and it seems everyone has a reason or a connection to Loren Lee. Tabby and Sage are burning the candle at both ends--but will it be enough to keep their friends safe and find this killer? Or will they be burned by their efforts?